PALATE FRACTURE PROFILE IN PLASTIC RECONSTRUCTIVE AND AESTHETIC SURGERY OF DR. SOETOMO GENERAL ACADEMIC HOSPITAL: JANUARY 2012- DECEMBER 2017 - N., Priscilla Valentine; Budi, Agus Santoso; Zarasade, Lobredia (Universitas Airlangga, 2019)
Highlights: The demographic data of patients with palate fractures is young adult men aged 19-30 years, the most common of palatal fracture type is parasagittal type, and causes of trauma being traffic accidents. The use of transmolar wiring and plating, occlusion was achieved well. Abstract: Introduction: Palatal fractures are often associated with maxillofacial fractures and Le Fort fractures. The diagnosis and management of palatal fractures in the midface area is a challenge for a plastic surgeon in restoring function and aesthetics. With the results of this study, it is expected to be a database of maxillofacial fractures treated at SMF Reconstructive Plastic Surgery and Aesthetic Dr. Soetomo General Academic Hospital, Surabaya and gave the ability to make a fast and precise diagnosis for time and technical maxillofacial fractures. Methods: This study uses medical record data for all patients diagnosed with palatal fractures in Dr. Soetomo General Academic Hospital, Surabaya during January 2012 to December 2017. The variables studied were demographic data including sex, age, mechanism of occurrence of accidents, types of fractures, management, complications that occur and length of treatment. Discussion: There were 82 patients with palatal fractures, with traffic accidents being the most common cause of palate fracture (n=61) followed by workplace accidents and households in second place (12 and 9%). Most sufferers were men (68%), women (14%) with the highest age range of men aged 19-30 years who were followed by ages 31-45. The most were parasagittal fractures (56%), then Sagittal (15%), paraalveolar (9%), alveolar (1%), comminutive (1%). no fractures with anterior and posterolateral alveolar types, posterolateral type or transverse type fractures. Hospitalization period with plating (12 days), transmolar wiring (10.6 days), and conservative (13.8 days). Conclusions: In this study assessed the experience in the reconstruction and aesthetic plastic surgery department of Dr. Soetomo General Academic Hospital regarding palatal fractures and accompanying demographic data. The type of fracture that occurs is also related to the management performed. Incomplete medical records caused problems in this study.